2021
DOI: 10.5334/gh.1035
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Feasibility of Same Day Discharge Strategy for Primary Percutaneous Coronary Intervention

Abstract: Background:The strategy for early discharge after primary percutaneous coronary intervention (PCI) could have substantial financial benefits, especially in low-middle income countries. However, there is a lack of local evidence on feasibility and safety of the strategy for early discharge. Therefore, the aim of this study was to assess the safety of early discharge after primary PCI in selected low-risk patients in the population of Karachi, Pakistan. Methods: In this study 600 consecutive low-risk patients wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 28 publications
(51 reference statements)
0
19
0
Order By: Relevance
“…This prospective observational cohort study is a sub-group analysis of a previously reported study by Shah JA et al [ 10 ]. This study was conducted at a tertiary care cardiac hospital of Karachi, Pakistan between August 2019 and July 2020.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…This prospective observational cohort study is a sub-group analysis of a previously reported study by Shah JA et al [ 10 ]. This study was conducted at a tertiary care cardiac hospital of Karachi, Pakistan between August 2019 and July 2020.…”
Section: Methodsmentioning
confidence: 99%
“…This study was approved by the ethical review board of the institution and consent for participation, and follow-up was taken from all the patients. A detailed descriptions of patient recruitment, management, and evaluation criteria are presented elsewhere [ 10 ]. Patients with myocardial infarction complicated by cardiogenic shock, atrioventricular (AV) block, or history of prior cardiac surgery or intervention or patients lost to follow-up at 30-day (3.4% (17)) [ 10 ] were excluded from the study.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations